2019
DOI: 10.1109/access.2019.2955639
|View full text |Cite
|
Sign up to set email alerts
|

Development of Serious Games for Teaching Information Security Courses

Abstract: Serious games have been used effectively in many educational domains. Games may be utilized efficiently to attract students to information security track. Learning practical knowledge about information security from a game is more engaging and less time consuming than learning through textbooks. Games that closely emulate real-world systems can improve learning about computer security above and beyond just reading technical documents and textbooks. From this perspective, this paper presents six serious games w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 46 publications
1
16
0
Order By: Relevance
“…It was also encouraging to find that 65.2% (73) stated that they would return to SherLOCKED to help revise for the exam and more generally, that 84.8% (95) saw playing serious games as a good way to help them to learn. These positive points align well with other existing research about the current and future value of gamification when applied to higher education learning [14]. Fig.…”
Section: Resultssupporting
confidence: 90%
See 4 more Smart Citations
“…It was also encouraging to find that 65.2% (73) stated that they would return to SherLOCKED to help revise for the exam and more generally, that 84.8% (95) saw playing serious games as a good way to help them to learn. These positive points align well with other existing research about the current and future value of gamification when applied to higher education learning [14]. Fig.…”
Section: Resultssupporting
confidence: 90%
“…Theme A primary decision in designing a game is the theme on which to base it. Reflecting on current literature, we found that role-playing games often performed well and were preferred by students [14,17]. We then considered various types of roles and settled on a detective theme with an animated detective as the player's character and three cases to solve, based on the three levels (and areas of content) identified earlier.…”
Section: The Gamementioning
confidence: 99%
See 3 more Smart Citations